If I didn´t care, one more kiss [feat_ 2019’s “She (and the space of painting)”] - Sabino, Isabel (Farol, 2019)
The 2019 text entitled “She (and the space of painting)”, produced in a parallel creative process for a painting exhibition, focuses on contemporary art theory, film, female characters, literature, poetry, music and, especially, on pictorial space from the feminine perspective. Now, it is reissued here, choosing one of the paintings made, already exposed, and a song underlying it as symptomatic of the perspective of confinement by the pandemic crisis.